2020
DOI: 10.1136/bmjopen-2020-038148
|View full text |Cite
|
Sign up to set email alerts
|

Imputing HbA1c from capillary blood glucose levels in patients with type 2 diabetes in Sri Lanka: a cross-sectional study

Abstract: ObjectiveTo develop a population-specific methodology for estimating glycaemic control that optimises resource allocation for patients with diabetes in rural Sri Lanka.DesignCross-sectional study.SettingTrincomalee, Sri Lanka.ParticipantsPatients with non-insulin-treated type 2 diabetes (n=220) from three hospitals in Trincomalee, Sri Lanka.Outcome measureCross-validation was used to build and validate linear regression models to identify predictors of haemoglobin A1c (HbA1c). Validation of models that regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although, despite available diagnostic testing, studies have shown that they are not optimally used in managing patient care, and tools to bridge the diagnostic–treatment divide are needed 41 42. MAAAs offer one approach to help bridge this gap and can be coupled with simple paper-based tools (eg, nomograms) to more complex mobile app-based tools or lightweight, field-deployed (cloud-based) Laboratory Information Systems designed for use in LMICs 43 44. In addition to the use of MAAAs as a tool for CRC diagnosis, the approach could be adapted for the prediction of CRC prognosis and treatment outcomes as both the CBC and CMP profiles of patients have been associated with disease stage, metastasis and treatment outcomes 45–47…”
Section: Ai and ML Approachesmentioning
confidence: 99%
“…Although, despite available diagnostic testing, studies have shown that they are not optimally used in managing patient care, and tools to bridge the diagnostic–treatment divide are needed 41 42. MAAAs offer one approach to help bridge this gap and can be coupled with simple paper-based tools (eg, nomograms) to more complex mobile app-based tools or lightweight, field-deployed (cloud-based) Laboratory Information Systems designed for use in LMICs 43 44. In addition to the use of MAAAs as a tool for CRC diagnosis, the approach could be adapted for the prediction of CRC prognosis and treatment outcomes as both the CBC and CMP profiles of patients have been associated with disease stage, metastasis and treatment outcomes 45–47…”
Section: Ai and ML Approachesmentioning
confidence: 99%